27-hydroxycholesterol acts on estrogen receptor α expressed by POMC neurons in the arcuate nucleus to modulate feeding behavior - Hui, Ye (2024)
Oxysterols are metabolites of cholesterol that regulate cholesterol homeostasis. Among these, the most abundant oxysterol is 27-hydroxycholesterol (27HC), which can cross the blood-brain barrier. Because 27HC functions as an endogenous selective estrogen receptor modulator, we hypothesize that 27HC binds to the estrogen receptor α (ERα) in the brain to regulate energy balance. Supporting this view, we found that delivering 27HC to the brain reduced food intake and activated proopiomelanocortin (POMC) neurons in the arcuate nucleus of the hypothalamus (POMCARH) in an ERα-dependent manner. In addition, we observed that inhibiting brain ERα, deleting ERα in POMC neurons, or chemogenetic inhibition of POMCARH neurons blocked the anorexigenic effects of 27HC. Mechanistically, we further revealed that 27HC stimulates POMCARH neurons by inhibiting the small conductance of the calcium-activated potassium (SK) channel. Together, our findings suggest that 27HC, through its interaction with ERα and modulation of the SK channel, inhibits food intake as a negative feedback mechanism against a surge in circulating cholesterol.